Management of Islamic Religious Education Learning in Integrated Schools - Ace Nurasa; Wawan Ridwan; Uus Ruswandi; Bambang Samsul Arifin (Edumaspul: Jurnal Pendidikan, 2022)
This study aims to determine the management of PAI learning in Integrated Islamic Schools. The research location is at the Integrated Islamic Middle School Nurul Azmi Tanjungsari Sumedang. This research method uses a qualitative approach that is descriptive analysis with a case study approach. The research subjects were school principals, vice principals and teachers. While the data collection techniques using interviews, observation and documentation. The results of this research are that learning PAI subjects is combined with other subjects including general subjects, so each subject must contain its religious education, and for learning not only in class it can be used in a school environment that allows it to be used for learning such as mosques, in rice fields, in the field and others. With the 13th Curriculum of PAI learning at SMP IT Nurul Azmi from the Ministry of Religion plus material on aqidah, morals, the Qur'an Hadith takes common religious sources such as the book of Bulugul Marom and others without taking the teaching materials used by MTs.